Training in cognitive behavioural interventions on acute psychiatric inpatient wards - McCann, Edward; Bowers, Len (My University, 2005)
There has been a drive towards addressing the types of care and therapeutic interventions available to people with serious mental illness, which is reflected in the latest government mental health policy initiatives. Recent evidence strongly supports the implementation of psychological and social interventions for people with psychosis, and in particular the use of cognitive behavioural techniques. Until now, the main focus has been on people living in the community. This study examines the delivery of psychosocial interventions training to qualified psychiatric nurses and unqualified staff on seven acute psychiatric admission wards in London, UK. The approach had the strength of on-site delivery, follow-up role modelling of the interventions and clinical supervision. Despite this, in some cases the training was less successful, mainly because of staffing and leadership weaknesses. The impact of training in these methods and the implications for mental health education and practice development are discussed.
PUBLISHED
Keywords: training; psychosocial interventions; schizophrenia; psychosis; Cognitive behavioural interventions; psychiatric inpatients; Psychiatric nursing education; INPATIENTS; SCHIZOPHRENIA